Reliability and Availability Analysis of Some Systems with Common-Cause Failures Using SPICE Circuit Simulation Program - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components, 1999)
The effectiveness of SPICE circuit simulation program in calculating probabilities, reliability, steady-state availability and mean-time to failure of repairable systems described by Markov models is demonstrated. Two examples are presented. The first example is a warm standby system with common-cause failures and human errors. The second example is a non-identical unit parallel system with common-cause failures. In both cases recourse to numerical solution is inevitable to obtain the Laplace transforms of the probabilities. Results obtained using SPICE are compared with previously published results obtained using the Laplace transform method. Full SPICE listings are included.